Molecular genetics and phylogeny of Ephippigera species group of genus Saga Charpentier, 1825 (Orthoptera: Ensifera: Saginae) in Anatolia - Bi̇ni̇ci̇ Burcu; Şi̇ri̇n Deni̇z; Taylan Mehmet Sai̇t (Zootaxa, 2021)
The genus Saga, one of the largest predatory bush crickets and insects in the Palearctic region, is represented by nine species in Anatolia. According to the morphological and bioacoustics evaluations of the Ephippigera species group belonging to the Saga genus, it consists of three species: S. ephippigera, S. syriaca, and S. hakkarica. To the present, however, there is no molecular genetic research on this species group. In our study, by using the 16S rDNA gene sequences, the molecular phylogeny of this species group is revealed and the morphological species hypotheses has been tested. In the study, specimens belonging to S. ephippigera, S. syriaca, and S. hakkarica were collected between the years of 2018 and 2020 with sweep netting; the DNA isolation, polymerase chain reactions, purifications and double-stranded sequencing were performed to obtain 16S rDNA gene sequences. Sequences were evaluated phylogenetically by performing alignment, phylogenetic analysis (Maximum Likelihood and Bayesian Inference), and dating of cladogenetic events, respectively. The monophyletic and species hypotheses of all three species have been supported by molecular data. It has been determined that the S. ephippigera species is the origin lineages of the Ephippigera species group which diverged approximately 0.4 million years ago; it has been also revealed that the climatic changes in the glacial and inter-glacial periods in the Middle Pleistocene period affected greatly the evolution of the species group.